Microscopic polyangiitis presenting with persistent cough and hemoptysis in pediatrics: A case report and review of the literature - Zhu, Yantong; Zheng, Xiangrong (Frontiers in Oncology, 2022)
Background Microscopic polyangiitis (MPA) is a necrotizing vasculitis that involves small- and medium-sized vessels and is associated with the presence of antineutrophil cytoplasmic antibodies with a perinuclear staining pattern (p-ANCA). The kidney and lungs are the organs primarily affected. MPA is rare in children and is easily misdiagnosed. Below is a complete case history of the course of the disease. Case presentation An 11-year-old girl with a 1-month history of cough and hemoptysis showed no improvement after imipenem-cilastatin treatment. p-ANCA and microscopic hematuria and proteinuria were positive, and a chest CT revealed an area of shadow in the bilateral lower lobe of the lungs. Renal biopsies showed crescentic glomerulonephritis, and MPA was diagnosed based on these criteria. The patient exhibited dramatic clinical and imaging improvements after immunosuppressive treatment. Conclusion The organs most commonly involved in MPA in children are the lungs, kidneys, skin, nervous system organs, and organs of the gastrointestinal tract. Careful examination should be carried out in these patients while biopsies of the kidney or any other organs remain the gold standard for diagnostic purposes. Pulmonary involvement may be the initial symptom of the disease and should not be confused with pneumonia. A urinalysis should be performed in patients with hemoptysis. Antibiotics should be used with caution.